2021
DOI: 10.3390/plants10040743
|View full text |Cite
|
Sign up to set email alerts
|

Design a Database of Italian Vascular Alimurgic Flora (AlimurgITA): Preliminary Results

Abstract: Despite the large number of data published in Italy on WEPs, there is no database providing a complete knowledge framework. Hence the need to design a database of the Italian alimurgic flora: AlimurgITA. Only strictly alimurgic taxa were chosen, excluding casual alien and cultivated ones. The collected data come from an archive of 358 texts (books and scientific articles) from 1918 to date, chosen with appropriate criteria. For each taxon, the part of the plant used, the method of use, the chorotype, the biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 74 publications
1
23
0
Order By: Relevance
“…Four different leafy vegetables, chosen on the basis of their wide diffusion in several traditional recipes of the Mediterranean diet [ 24 ], were investigated. They were two wild edible plants, belonging to Sonchus species, Sonchus asper L. Hill and Sonchus oleraceus L. (Asteraceae), and two more commercial ones, spinach ( Spinacia oleracea L.) and chicory ( Cichorium intybus L.).…”
Section: Methodsmentioning
confidence: 99%
“…Four different leafy vegetables, chosen on the basis of their wide diffusion in several traditional recipes of the Mediterranean diet [ 24 ], were investigated. They were two wild edible plants, belonging to Sonchus species, Sonchus asper L. Hill and Sonchus oleraceus L. (Asteraceae), and two more commercial ones, spinach ( Spinacia oleracea L.) and chicory ( Cichorium intybus L.).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, the increased interest in ethnobotanical studies of local wild plants [7,12] emerged out of a need to create new products for the food industry with beneficial properties, as well as for sustainable agriculture because of the low impact of their cultivation on the environment [2,[13][14][15][16]. In this scenario, knowledge of edible plants biodiversity available in the local food tradition, and of new pathways for the eco-sustainable enhancement of food resources, constitute crucial aspects to intercept in marginal or valuable areas (e.g., Nature Reserves and National Parks), in full agreement with the EU's biodiversity strategy plan for 2030 [17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Guarrera [34] reported a total of 580 food species for the whole of Italy, while Guarrera and Savo [29] stated that 276 wild taxa are used in traditional vegetable mixtures in Italy. More recently, the review carried out by Paura et al [39] reported the use of 1103 wild food taxa for the whole of Italy. Biscotti et al [40] and Pasta et al [41] summarized the ethnobotanical use of 214 and 292 wild food taxa for the Apulia and Sicily regions, respectively.…”
Section: General Datamentioning
confidence: 99%
“…Moreover, our results provide a relevant and novel contribution to the knowledge of food plants in Tuscany and in Italy by including original data from graduation theses. It is important to point out that the review carried out by Paura et al [39] counted a total of 341 food species for Tuscany. Unfortunately, this database is not accessible online and it was not possible to compare our data to those recorded by these authors.…”
Section: General Datamentioning
confidence: 99%